In the diffuse large B-cell lymphoma microenvironment, SIRT1 is upregulated and correlated with a pro-inflammatory macrophage signature and autophagy-related gene expression - Resanoa, Miguel; Azcoaga, Peio; Salvador, Naike; Delgado, Alba; Rodiño, Claudia; Schoenhals, Matthieu; Braza, Mounia S. (Frontiers in Immunology, 2026)
Diffuse large B-cell lymphoma (DLBCL) is an aggressive and heterogeneous blood cancer and one of the most frequent non-Hodgkin lymphomas of B-cell origin. As it has a complex, macrophage-rich immune microenvironment, we wanted to determine the role of autophagy, in which incoming threats are sequestered/removed and damaged cell constituents and debris are recycled, and metabolic sensors, such as sirtuins (SIRTs), in this cancer. Therefore, we determined the autophagy status in primary DLBCL samples using publicly available transcriptomic data and validated these results by immunohistochemistry and immunofluorescence analyses of patients’ tissue microarrays. We found that autophagy components and SIRTs were upregulated in the DLBCL microenvironment, particularly in the resting (M0) and pro-inflammatory (M1) macrophage subtypes. Moreover, the expression of autophagy factors was positively correlated with that of SIRT1 and SIRT3, which were both upregulated in macrophages. Specifically, SIRT1 was correlated with the expression of CD80 (M1 macrophage marker) and SIRT3 with the expression of M-CSF (M2 macrophage marker). Overall, in DLBCL samples, we observed a positive correlation between the expression of SIRT1 and of inflammation-related genes, and between SIRT3 and immunosuppression-related genes. Lastly, we confirmed in an independent DLBCL cohort that only SIRT1, but not SIRT3, was significantly associated with autophagy-related immune cells. Our study identified SIRT expression in macrophages of the DLBCL environment and specifically the importance of SIRT1 in the DLBCL M1 macrophage immune microenvironment. This opens an avenue for the potential translational exploitation of SIRT1 modulation as therapeutic target in this hematological malignancy.